Pengaruh Struktur Kepemilikan Terhadap Kebijakan Dividen dan Manajemen Laba pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Siti Kholila; Nur Ajizah (MES Bogor, 2025)
This research aims to examine the influence of ownership structure on dividend policy and earnings management in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This research uses a quantitative research approach. The research sample selection used purposive sampling of 226 companies, and a sample of 11 manufacturing companies was obtained. The data source for this research uses secondary data originating from the financial reports of manufacturing companies listed on the Indonesia Stock Exchange (BEI). Statistical tests and data processing were carried out using Partial Least Square (WarpPLS). The research results show (1) Ownership structure has a significant negative effect on dividend policy. (2) Ownership structure has a significant positive effect on earnings management. (3) Dividend policy has no effect on earnings management.